Analysis of Albert Bandura's Social Cognitive Theory and Its Development in Islamic Religious Education - Irhas Sabililhaq; Nursiah; Ajusman; Misbahul Munir (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research aims to explain the concept of Albert Bandura's theory and its development in Islamic religious education. The research is motivated by many other learning theories that have not focused on the origin of behavior, especially those that come from outside a person. On the other hand, Albert Bandura, with the concept of self-efficacy and imitation, has discussed this in detail in his social cognitive theory. The method used is qualitative with the type of literature study or library research. The results of the study stated that Albert Bandura's theory is famous for its social learning theory that emphasizes cognition and evaluation. It includes modeling (live and symbolic) and self-efficacy, as well as research on the aggressive behavior of children who imitate aggression from adult models. In “Aggression: A Social Learning Analysis,” Bandura explains that aggression is learned through observation and reinforcement, as shown in the Bobo Doll experiment. Bandura's social cognitive theory emphasizes the function of self-regulation, learning in the social environment, visual and verbal learning outcomes, and the importance of imitation and role models, which requires educators, parents, and community leaders to be good examples. In Islamic Religious Education (PAI), Bandura's theory can be applied through the principles of modeling, self-efficacy, and mentoring. The Prophet is the ultimate role model, and the family should be the real example for children. PAI should teach the principles and resilience of faith to avoid the negative influence of the digital era with the guidance of parents and teachers so that the content absorbed by students is positive.